Study ot the establishment of epithelial polarity: search for new proteins that interact with aPKC - Calero-Cuenca, Francisco Javier; Sotillos-Martín, Sol (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2013)
Most eukaryotic cells are polarized with an asymmetric distribution of molecules and organelles resulting in different functional regions required for cell physiology. It is essential the regulation of this polarity in space and time to coordinate changes in cell morphology with proliferation and morphogenetic movements required for the organism development1. This regulation is accomplished by signalling pathways, which in many cases are regulated by the subcellular localization of their components. Consequently, the understanding of the relation between signalling pathways and cell polarity is crucial for the knowledge of how signals are integrated to induce morphogenesis but also how are modified in aberrant processes as those occurring in cancer. The atypical protein kinase C (aPKC) is a critical protein in cell polarity establishment and maintenance, and also participate in many other processes like migration o asymmetric cell division. aPKC has an enzymatic activity and can regulate different signaling pathways in the cell. In all these processes aPKC interacts with different regulators and modifies different substrates. In addition, aPKC is an oncogene. To understand how cell polarity is established, maintained and modified and also how this polarity can regulate signalling processes we have focused on to find out new proteins that interact with aPKC. D. St Johnston and B. Sanson, Current opinion in cell biology 23 (5), 540 (2011). 540 (2011). T. Vaccari and D. Bilder, Molecular oncology 3 (4), 354 (2009).